Rethinking readiness : a brief guide to twenty-first-century megadisasters - Schlegelmilch, Jeffrey (New York : Columbia University Press, 2020)
"As human society continues to develop, we have increased the risk of large-scale disasters. From health care to infrastructure to national security, systems designed to keep us safe have also heightened the potential for catastrophe. The constant pressure of climate change, geopolitical conflict, and our tendency to ignore what is hard to grasp exacerbates potential dangers. How can we prepare for and prevent the twenty-first-century disasters on the horizon? Rethinking Readiness offers an expert introduction to human-made threats and vulnerabilities, with a focus on opportunities to reimagine how we approach disaster preparedness. Jeff Schlegelmilch identifies and explores the most critical threats facing the world today, detailing the dangers of pandemics, climate change, infrastructure collapse, cyberattacks, and nuclear conflict. Drawing on the latest research from leading experts, he provides an accessible overview of the causes and potential effects of these looming megadisasters. The book highlights the potential for building resilient, adaptable, and sustainable systems so that we can be better prepared to respond to and recover from future crises. Thoroughly grounded in scientific and policy expertise, Rethinking Readiness is an essential guide to this century's biggest challenges in disaster management"-- Provided by publisher.
Includes bibliographical references (p. [145] - 169) and index.
Keywords: Emergency management; Natural disasters; Risk management; Natural disaster warning systems